The development of a story recall test for distinguishing between Alzheimer’s disease and mild cognitive impairment in Thai cohort - Natinee Na Chiangmai; Peera Wongupparaj; Pattrawadee Makmee; Claudio Mulatti; Remo Job (Humanities & Social Sciences Communications)
Abstract The story recall task requires complex cognitive functions since it imitates everyday communication. It provides promising discrimination between individuals with cognition intact, mild cognitive impairment (MCI), and Alzheimer’s disease (AD). This study aimed to develop and examine the validity of the Thai Story Recall Test (TSR) in community-dwelling Thai older adults. A total of 98 participants were recruited and underwent the TSR with the stimulus story in the Thai context along with the neuropsychological tests including the Montreal Cognitive Assessment (MoCA), verbal fluency, and digit span tasks. Partial correlation analyses, controlling for education, demonstrated that the MoCA marginally and significantly correlates with the immediate recall scores, whereas delayed recall scores showed a statistically significant moderate correlation with the MoCA. Specifically, only delayed recall scores were statistically significant in differentiating between stages of AD pathology. Further analysis revealed that delayed recall, backward digit span, and letter fluency tasks could significantly contribute to a discriminant function. It successfully classified participants with cognitive impairment (MCI and AD together) with an accuracy of 0.87, a sensitivity of 83.3%, and a specificity of 77.1%. Thus, delayed recall in the TSR has the potential to detect cognitive deficits in Thai older adults, especially when combined with other neuropsychological measures. Moreover, screening tools for AD should encompass not only memory assessment but also language and attention.